The dual GLP‐1 and GLP‐2 receptor agonist dapiglutide promotes barrier function in murine short bowel. Issue 1 (17th May 2022) - Reiner, Johannes; Thiery, Johanna; Held, Jascha; Berlin, Peggy; Skarbaliene, Jolanta; Vollmar, Brigitte; Jaster, Robert; Eriksson, Per‐Olof; Lamprecht, Georg; Witte, Maria
Abstract: Short bowel syndrome can occur after extensive intestinal resection, causing intestinal insufficiency or intestinal failure, which requires long‐term parenteral nutrition. Glucagon‐like peptide‐2 (GLP‐2) pharmacotherapy is now clinically used to reduce the disease burden of intestinal failure. However, many patients still cannot be weaned off from parenteral nutrition completely. The novel dual GLP‐1 and GLP‐2 receptor agonist dapiglutide has previously been shown to be highly effective in a preclinical murine short bowel model. Here, we studied the effects of dapiglutide on intestinal epithelial barrier function. In the jejunum, dapiglutide increased claudin‐7 expression and tightened the paracellular tight junction leak pathway. At the same time, dapiglutide promoted paracellular tight junction cation size selectivity in the jejunum. This was paralleled by extension of the cation selective tight junction proteins claudin‐2 and claudin‐10b and preserved claudin‐15 expression and localization along the crypt–villus axis in the jejunum. In the colon, no barrier effects from dapiglutide were observed. In the colon, dapiglutide attenuated the short bowel–associated, compensatorily increased epithelial sodium channel activity, likely secondary, by improved volume status. Future studies are needed to address the intestinal adaptation of the colon. Abstract : Short bowel (SB) syndrome can occur after extensive intestinal resection, causing intestinal insufficiency or intestinal failure, requiring long‐term parenteral nutrition. Glucagon‐like peptide‐2 (GLP‐2) pharmacotherapy is now used to treat intestinal failure. The novel dual GLP‐1 and GLP‐2 receptor agonist dapiglutide mediates strong jejunum villus growth, promotes jejunum barrier function to leak, and increases jejunum cation permeability. These effects strongly counteract SB‐associated diarrhea and volume depletion